Beneficial Effect of Sumbawa Wild Horse Milk Yogurt on Lipid Profile and Cardiovascular Risk in Rats on a High-Cholesterol Diet - Laksmi Nur Fajriani; Ni Made Wiasty Sukanty; Dea Pratiwi Silpia Putri; Esya Mariska Febriani (Biology, Medicine, & Natural Product Chemistry, 2025)
Cardiovascular disease (CVD) is a leading cause of death in Indonesia, with a high prevalence due to a high-cholesterol diet that triggers hypercholesterolemia. The use of statins as a long-term pharmacological therapy often causes side effects, so safe natural alternatives are needed. Sumbawa wild horse milk is a potential functional food source that contains essential fatty acids and lactic acid bacteria (LAB), which have probiotic potential. This study aims to evaluate the effect of Sumbawa wild horse milk yogurt on total cholesterol, HDL, LDL, Atherogenic Index (AI), and Cardiac Risk Ratio (CRR) levels in hypercholesterolemic male Wistar rats. A total of 30 rats were divided into six groups: normal, positive control (high-cholesterol diet), negative control (simvastatin), and three treatment groups, T1, T2, and T3, with doses of Sumbawa wild horse milk yogurt of 2, 3, and 4 ml/day, respectively, for 28 days. The results showed a significant decrease in total cholesterol levels (p = 0.006), with the lowest levels observed in the T3 treatment group (95.25 ± 20.17 mg/dL). Although HDL, LDL, IA, and CRR levels did not show significant differences (p > 0.05), a trend of improvement in lipid profiles was observed in the treatment group, characterized by an increase in HDL and a decrease in LDL, AI, and CRR compared to the positive control. The mechanism of cholesterol reduction is thought to be mediated through the activity of LAB, which assimilates cholesterol, facilitates bile acid deconjugation, and produces short-chain fatty acids that inhibit cholesterol absorption. Thus, Sumbawa wild horse milk yogurt has the potential to be a hypocholesterolemic functional food that can improve lipid profiles and reduce the risk of atherosclerosis and CVD.